Profile of Education Level and Understanding of Insulin Therapy in Type 2 Diabetes Mellitus Patients With Insulin Therapy at RSUD dr. M. Soewandhi Surabaya - Cintantya, Danastri Tiara; Prajitno, Jongky Hendro; Handayani, Samsriyaningsih (International Journal of Health and Medicine, 2025)
This study examines the relationship between education level and understanding of insulin therapy among type 2 diabetes mellitus patients undergoing insulin therapy at RSUD dr. M. Soewandhi Surabaya. Using a descriptive observational method with a cross-sectional design, data were collected from interviews and medical record observations from 100 patients aged 15-64. The findings reveal that most patients had low educational backgrounds, with 27% never attending school and 39% only completing high school. Regarding insulin therapy comprehension, 10% demonstrated good understanding, 55% moderate, and 35% poor. The highest comprehension was insulin usage rules, while the lowest was injection techniques. The study underscores the need for tailored health education to improve patient understanding, particularly for low-education groups. Limitations of the study include the single-site setting and potential response biases from interviews. Future research should expand to include diverse populations and examine non-educational factors influencing therapy comprehension, such as cultural and economic conditions.